Dual‐extrusion 3D printing of anatomical models for education. Issue 1 (14th September 2017) - Smith, Michelle L.; Jones, James F.X.
Abstract : Two material 3D printing is becoming increasingly popular, inexpensive and accessible. In this paper, freely available printable files and dual extrusion fused deposition modelling were combined to create a number of functional anatomical models. To represent muscle and bone FilaFlex 3D flexible filament and polylactic acid (PLA) filament were extruded respectively via a single 0.4 mm nozzle using a Big Builder printer. For each filament, cubes (5 mm 3 ) were printed and analyzed for X, Y, and Z accuracy. The PLA printed cubes resulted in errors averaging just 1.2% across all directions but for FilaFlex 3D printed cubes the errors were statistically significantly greater (average of 3.2%). As an exemplar, a focus was placed on the muscles, bones and cartilage of upper airway and neck. The resulting single prints combined flexible and hard structures. A single print model of the vocal cords was constructed which permitted movement of the arytenoids on the cricoid cartilage and served to illustrate the action of intrinsic laryngeal muscles. As University libraries become increasingly engaged in offering inexpensive 3D printing services it may soon become common place for both student and educator to access websites, download free models or 3D body parts and only pay the costs of print consumables. Novel models can be manufactured as dissectible, functional multi‐layered units and offer rich possibilities for sectional and/or reduced anatomy. This approach can liberate the anatomist from constraints of inflexible hard models or plastinated specimens and engage in the design of class specific models of the future. Anat Sci Educ 11: 65–72. © 2017 American Association of Anatomists.